Connective tissue disease with macrophage activation syndrome: A case report. Issue 51 (23rd December 2022) - Chen, Qu; Zhang, Qiushuang; Wang, Xuebin
Abstract : Rationale: Macrophage activation syndrome (MAS), or secondary hemophagocytic lymphocytosis (sHLH), is a rare systemic inflammatory response syndrome that is fatal. Adult patients lack clear criteria for diagnosis and treatment, primarily derived from guidelines and protocols for treating family hemophagocytic lymphocytosis and systemic juvenile idiopathic arthritis (sJIA)-related MAS in children or from retrospective case reports. As a subtype of sHLH, MAS has a clinical presentation like sHLH, but treatment varies. Herein, we report the case of a 40-year-old female with MAS caused by a connective tissue disease. Patient concerns: The patient presented to the Rheumatology and Immunology Clinic with recurrent fever and rash, and MAS was confirmed after a series of examinations. The patient had no significant effect after treatment with JAK inhibitors, but after the use of the IL-6 inhibitor tocilizumab, the fever and rash were significantly reduced, and laboratory indicators returned to normal levels. Diagnosis: Considering the patient's condition and laboratory test results, we judged that the patient had connective tissue disease with MAS. Interventions: We gave sequential treatment of tocilizumab. Outcomes: ALL indicators are mostly back to normal when the patient was monitored at the outpatient clinic. Lessons: MAS/HLH lacks clear criteria for diagnosis or treatment in adult patients and is extremely difficult to distinguish from bacterial sepsis or other systemic inflammatory response syndromes. Consequently, early diagnosis and treatment are indispensable for enhancing patient survival.